Diffuse malignant peritoneal mesothelioma: Evaluation of systemic chemotherapy with comprehensive treatment through the RENAPE Database: Multi-Institutional Retrospective Study. (September 2016) - Kepenekian, V.; Elias, D.; Passot, G.; Mery, E.; Goere, D.; Delroeux, D.; Quenet, F.; Ferron, G.; Pezet, D.; Guilloit, J.M.; Meeus, P.; Pocard, M.; et al.
Abstract: Purpose: Diffuse malignant peritoneal mesothelioma (DMPM) is a severe disease with mainly locoregional evolution. Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) is the reported treatment with the longest survival. The aim of this study was to evaluate the impact of perioperative systemic chemotherapy strategies on survival and postoperative outcomes in patients with DMPM treated with curative intent with CRS-HIPEC, using a multi-institutional database: the French RENAPE network. Patients and methods: From 1991 to 2014, 126 DMPM patients underwent CRS-HIPEC at 20 tertiary centres. The population was divided into four groups according to perioperative treatment: only neoadjuvant chemotherapy (NA), only adjuvant chemotherapy (ADJ), perioperative chemotherapy (PO) and no chemotherapy before or after CRS-HIPEC (NoC). Results: All groups (NA: n = 42; ADJ: n = 16; PO: n = 16; NoC: n = 48) were comparable regarding clinicopathological data and main DMPM prognostic factors. After a median follow-up of 61 months, the 5-year overall survival (OS) was 40%, 67%, 62% and 56% in NA, ADJ, PO and NoC groups, respectively ( P = 0.049). Major complications occurred for 41%, 45%, 35% and 41% of patients from NA, ADJ, PO and NoC groups, respectively ( P = 0.299). In multivariate analysis, NA was independently associated with worse OS (hazard ratio, 2.30; 95% confidence interval, 1.07–4.94; P = 0.033). Conclusion: This retrospective study suggests that adjuvant chemotherapy may delay recurrence and improve survival and that NA may impact negatively the survival for patients with DMPM who underwent CRS-HIPEC with curative intent. Upfront CRS and HIPEC should be considered when achievable, waiting for stronger level of scientific evidence. Highlights: The combination of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) is the cornerstone of a curative treatment strategy for diffuse malignant peritoneal mesothelioma (DMPM). All patients with a diagnostic of DMPM should be evaluated prior any treatment in an expert peritoneal surface malignancies (PSM) centre. Upfront surgery appears preferable to neoadjuvant chemotherapy in patients amenable to complete CRS.